Implications In EFL Teaching - Kalayo Hasibuan Hasibuan; Hanna Rahmah Pratiwi Pratiwi; Ilma Hidayah Hidayah; Khusnul Sofia Sofia (Journal of Innovative and Creativity, 2025)
The objectives of this research are to explore the implications of integrating Islamic values in English as a Foreign Language (EFL) teaching, focusing on how these values influence teaching practices and student communication skills. This qualitative study examines three main aspects: the integration of Islamic values into EFL instruction, the use of culturally appropriate examples aligned with Islamic principles, and the development of effective and polite language skills among learners. The sample includes EFL educators and students from Islamic educational settings. Data were collected through interviews, classroom observations, and document analysis, and were analyzed using thematic analysis to uncover key patterns and insights. The findings indicate that incorporating Islamic values in EFL teaching enhances students’ cultural understanding and moral development, ensures the appropriateness of teaching materials, and promotes effective, respectful communication. The study concludes that EFL teaching in Islamic contexts should consistently embed religious values to foster both language proficiency and ethical awareness.